If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + 21 = m + -8 Combine like terms: -3 + 21 = 18 18 = m + -8 Reorder the terms: 18 = -8 + m Solving 18 = -8 + m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1m' to each side of the equation. 18 + -1m = -8 + m + -1m Combine like terms: m + -1m = 0 18 + -1m = -8 + 0 18 + -1m = -8 Add '-18' to each side of the equation. 18 + -18 + -1m = -8 + -18 Combine like terms: 18 + -18 = 0 0 + -1m = -8 + -18 -1m = -8 + -18 Combine like terms: -8 + -18 = -26 -1m = -26 Divide each side by '-1'. m = 26 Simplifying m = 26
| x*2-0.2x*4x-2400=0 | | 4x-8=5x-2(x+2) | | f(1.8)=2x*x-16x+63 | | x/x+4 | | 1/x+4 | | x-4/x-16 | | f(1.8)=2x*2x-16x+63 | | y/8=17 | | (x-9)(2x^2+x-3)= | | 5/12+1/2 | | 9y-12y=-10-14 | | .24y-4=.14y+2-.7y | | 1/15+3/5 | | 2/5+9/20 | | 8x-4=-29+3x | | x^4+81=18x^2 | | 8t+(3t-4t)= | | 9n-3y=-3 | | -11r-(5-6r)=-(6-3r)+1 | | 3x-7y=-15 | | 13/4(3x+3/4) | | 8(3x+2)/5=x+3 | | 3x-2x+6-1=4x+2 | | 2n-4y=-24 | | 4(y-2)/5=-2y | | 6x(2x-1)=9x+2(2-x) | | 6(x+3)/4=3x-2 | | -34(12-8)=-8 | | 3s-21=9+7s | | 7x+4=-4+3x+28 | | -7+4x=42 | | 8(x-4)-2=-34 |